Exploring The Relationship Between Language Skills and Academic Performance of Indonesian Students Abroad: A Multigroup SEM-PLS Approach - Malahayati, Aisyah Juliawulan; Sawitri, Yulia; Maizi, Hazful; Fadilla, Meutia (Jurnal Penelitian Inovatif, 2025)
Language barriers remain a critical challenge for Indonesian students pursuing higher education abroad, potentially hindering their academic success. This study aims to analyze the effect of language skills on academic performance using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with multigroup analysis. Data were collected through an online survey from 100 Indonesian STEM students studying in Asia and Europe, selected using probability sampling. The analysis confirmed a significant positive effect of language skills on academic performance (path coefficient = 0.464; p < 0.001). However, multigroup analysis showed no significant moderating effect of instruction language, study destination, or learning system (p > 0.05 for all groups). These findings highlight that language skills consistently influence academic outcomes across different contexts. The study provides empirical evidence to support the development of targeted language support programs and inclusive academic strategies for Indonesian students abroad.